2007
DOI: 10.1016/j.jaapos.2007.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Children’s Visual Function Questionnaire (CVFQ)

Abstract: The CVFQ subscales quantified meaningful differences among pediatric patient groups who were chosen to address key research questions commonly posed in ophthalmic clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 15 publications
(7 reference statements)
5
79
0
3
Order By: Relevance
“…This approach has been used more commonly in assessing outcomes of children or those with learning disabilities. 9 In recent years, the term 'quality-of-life' (QoL) has been widely used in vision rehabilitation outcome studies. There is no single definition of quality-of-life, and the parameters assessed are often context dependent.…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been used more commonly in assessing outcomes of children or those with learning disabilities. 9 In recent years, the term 'quality-of-life' (QoL) has been widely used in vision rehabilitation outcome studies. There is no single definition of quality-of-life, and the parameters assessed are often context dependent.…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
“…9,27,62,84 For example, the 25-item Cardiff Visual Ability Questionnaire for Children (CVAQC) assesses self-reported visual ability in children and young people with a visual impairment. 84 One important function of outcomes research is to assess the cost effectiveness of health and social care interventions so that policy makers can make judgments about a particular treatment/intervention.…”
Section: Outcome Measures For Assessing the Effectiveness Of A Sermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using parental proxy VR-QoL-tools such as the Children's Visual Function Questionnaire found that family impact and treatment difficulty scores are worse in families of children with unilateral compared with those with bilateral cataracts, and in those treated with an aphakic contact lens compared with those treated with an intraocular lens implant 9 . Bilateral congenital/infantile cataract is associated with reduced VR-QoL scores EYE-16-281R2 December 7, 2016 5 compared to healthy controls 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Visual ability and QOL measures that assess the impact of vision loss in children have been examined in a variety of pediatric eye diseases, with most designed to evaluate children between 8 and 18 years of age. [59][60][61][62][63] Using the review process developed by the REiNS Patient-Reported Outcomes Subcommittee (see Wolters et al, this supplement), we reviewed the available pediatric questionnaires. Of these, 2 examined visual ability rather than visionspecific QOL.…”
mentioning
confidence: 99%